2012
DOI: 10.1073/pnas.1217443109
|View full text |Cite
|
Sign up to set email alerts
|

Most rhesus macaques infected with the CCR5-tropic SHIV AD8 generate cross-reactive antibodies that neutralize multiple HIV-1 strains

Abstract: The induction of broadly reacting neutralizing antibodies has been a major goal of HIV vaccine research. Characterization of a pathogenic CCR5 (R5)-tropic SIV/HIV chimeric virus (SHIV) molecular clone (SHIV AD8-EO ) revealed that eight of eight infected animals developed cross-reactive neutralizing antibodies (NAbs) directed against an envelope glycoprotein derived from the heterologous HIV-1 DH12 strain. A panel of plasmas, collected from monkeys inoculated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(106 citation statements)
references
References 37 publications
2
104
0
Order By: Relevance
“…Although MN4/LSDQgtu is a CXCR4-tropic virus, it has clear potential for the establishment of a model system. MN4/LSDQgtu can be changed to a pathogenic CCR5-tropic virus through in vitro and in vivo approaches, as well documented by previous SHIV studies (68)(69)(70). It is also possible to generate entirely new CCR5-tropic HIV-1mt clones other than MN4/LSDQgtu derivatives on the basis of the key findings for Gag-CA and Vpu-TM in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Although MN4/LSDQgtu is a CXCR4-tropic virus, it has clear potential for the establishment of a model system. MN4/LSDQgtu can be changed to a pathogenic CCR5-tropic virus through in vitro and in vivo approaches, as well documented by previous SHIV studies (68)(69)(70). It is also possible to generate entirely new CCR5-tropic HIV-1mt clones other than MN4/LSDQgtu derivatives on the basis of the key findings for Gag-CA and Vpu-TM in this study.…”
Section: Discussionmentioning
confidence: 59%
“…5, while 62QR+5gtu grew significantly more poorly than 5gtu, 66SR+ 5gtu exhibited slightly more retarded growth kinetics relative to 5gtu. To see if this result is applicable to the other R5 -tropic viruses, and to confirm a generalization of above observation, we generated two other R5 -tropic HIV-1rmt clones carrying an env gene from a simian immunodeficiency virus/HIV-1 chimeric virus clone (SHIVAD8 -EH) (17) or from an HIV-1 clinical isolate. We then performed the M1.3S infection experiments as above.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we showed that the neutralization-resistant R5 tropic SHIV-MK38#818 molecular clone derived from SHIV-KS661 can cause stably persistent infection with high viral load via intrarectal inoculation despite the immune responses that occurred in the host. Currently, SHIV AD8 , categorized as a tier 2 neutralization-resistant phenotype, is widely used as a SHIV challenge virus for a variety of vaccine developments (Nishimura et al, 2010;Shingai et al, 2012Shingai et al, 2013;Gardner et al, 2015;Francica et al, 2015). However, use of SHIV AD8 as the only challenge virus is very risky for precise evaluation in vaccine candidates and anti-HIV-1 neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%